2010
DOI: 10.1002/ange.201003399
|View full text |Cite
|
Sign up to set email alerts
|

A Potent Trans‐Diimine Platinum Anticancer Complex Photoactivated by Visible Light

Abstract: Platin mit Licht aktiviert: Der inerte PtIV‐Diazidokomplex trans,trans,trans‐ [Pt(N3)2(OH)2(py)2] verwandelt sich bei der Bestrahlung mit geringen Dosen sichtbaren Lichts in einen potenten zytotoxischen Wirkstoff gegen Krebszellen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
98
0
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 81 publications
(104 citation statements)
references
References 31 publications
5
98
0
1
Order By: Relevance
“…Structures of platinum complexes studied in this work: trans , trans , trans -[Pt(N 3 ) 2 (OH) 2 (MA)(Py)] (1), trans , trans , trans -[Pt(N 3 ) 2 (OH) 2 (MA)(Tz)] (2), trans , trans , trans -[Pt(N 3 ) 2 (OH) 2 (NH 3 )(Py)] (3),5 trans , trans , trans -[Pt(N 3 ) 2 (OH) 2 (Py) 2 ] (4),6 trans -[PtCl 2 (MA)(Py)] (5), trans -[PtCl 2 (MA)(Tz)] (6), cisplatin (7), transplatin (8), and trans , trans , trans -[Pt(N 3 ) 2 (OH) 2 (NH 3 )(Tz)] (9).…”
Section: Introductionmentioning
confidence: 99%
“…Structures of platinum complexes studied in this work: trans , trans , trans -[Pt(N 3 ) 2 (OH) 2 (MA)(Py)] (1), trans , trans , trans -[Pt(N 3 ) 2 (OH) 2 (MA)(Tz)] (2), trans , trans , trans -[Pt(N 3 ) 2 (OH) 2 (NH 3 )(Py)] (3),5 trans , trans , trans -[Pt(N 3 ) 2 (OH) 2 (Py) 2 ] (4),6 trans -[PtCl 2 (MA)(Py)] (5), trans -[PtCl 2 (MA)(Tz)] (6), cisplatin (7), transplatin (8), and trans , trans , trans -[Pt(N 3 ) 2 (OH) 2 (NH 3 )(Tz)] (9).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, our strategy adds a new brick to the recently proposed approach of metal-based drug activation by light irradiation. [33][34][35]38] Very demonstrative work from Sadler et al [36] showed that irradiation at 420 nm of a platinum(IV) complex can make it one order of magnitude more cytotoxic than in the dark. Like in PDT, the wavelength of the light used to irradiate the tumor should indeed be high enough in the visible (or NIR) region to allow deep and harmless penetration of the photons in living tissues.…”
mentioning
confidence: 98%
“…Since photogenerated singlet oxygen ( 1 O 2 ) is a key species in photodynamic therapy (PDT), complexes 6 a-9 a have the potential to be developed into new PDT photosensitizers. [21] Nanostructures from 3 a and 8 a: We have previously reported that square-planar platinum(II) complexes can self-assemble into nanoscale molecular materials driven by intermolecular Pt II ···Pt II and ligand···ligand (p···p) interactions. [5b, 19] In this work, the continuous p···p interactions in 1D column chains revealed in the X-ray crystal structure of 3 a prompted us to study the morphology of the self-assembled structures from these complexes.…”
mentioning
confidence: 99%